2022
DOI: 10.3389/fenrg.2022.1026953
|View full text |Cite
|
Sign up to set email alerts
|

A study on a novel solar contribution evaluation method for the solar-aided coal-fired power generation system

Abstract: Solar-aided coal-fired power generation (SACPG) technology is an effective method of solar energy utilization. It could balance the demand of carbon dioxide emission reduction and renewable energy efficient power generation and promote carbon peaking and carbon neutralization. Accurate analysis of the share of solar energy in the unit output power could benefit the selection of the best integration scheme and exploitation of solar energy for further research. A novel solar contribution evaluation method of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Guo et al (2021) studied a multi-energy heating system combining solar, natural gas, and air energy, which can reduce economic costs and carbon emissions compared to conventional systems. Ancona et al (2021), Wang et al (2021) and Jiang et al (2022) concluded that the compound heating mode using different kinds of clean energy can improve energy efficiency and effectively reduce air pollution. 2) Research on clean heating models compounded by different equipment and facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Guo et al (2021) studied a multi-energy heating system combining solar, natural gas, and air energy, which can reduce economic costs and carbon emissions compared to conventional systems. Ancona et al (2021), Wang et al (2021) and Jiang et al (2022) concluded that the compound heating mode using different kinds of clean energy can improve energy efficiency and effectively reduce air pollution. 2) Research on clean heating models compounded by different equipment and facilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ongoing penetration of variable and intermittent renewable energy sources (RES), such as wind and solar energy, imposes additional and more critical requirements on power systems' flexibility [8]. Jiang Yue et al [9] analyzed the contribution of solar energy to the power generated by each steam turbine in a solarassisted coal-fired power generation system using SACPG technology. Furthermore, they explored the application potential of solar energy in coal-fired units.…”
Section: Introductionmentioning
confidence: 99%